Coupled models for spatial organization in development - Maini, P (1994)
Several simple models have been proposed to account for spatial organization in early development. Recently, a number of models have been proposed in which such patterning mechanisms are coupled. Here, we present a review of some of the latest theoretical results on such systems. In particular, we consider two cases: in one, the coupling of two mechanisms greatly enhances the robustness of the patterns produced; in the other, a hierarchical model exhibits spatially asymmetric patterns that are consistent with certain experimental observations.